Influences of oxidation-reduction potential on kefir: Microbial counts, organic acids, volatile compounds and sensory properties. (June 2021) - Bulat, Tugba; Topcu, Ali
Abstract: The effects of oxidation-reduction (redox) potential ( E h ) on microbiological and sensory characteristics, volatile compounds, and organic acids of kefir produced using wild or commercial culture were investigated during 21 d of storage. The E h of the milk was modified using reducing or oxidizing chemical agents. E h7 ( E h expresses at pH 7) values of control, reduced and oxidized kefirs produced using the wild kefir culture were −195.5, −206.1 and + 178.3 mV, while control, reduced and oxidized kefirs produced using the commercial kefir culture had E h7 values of −199.6, −208.1 and + 180.7 mV, respectively, on 1 d of storage. Generally, the viability of microorganisms in the kefirs was adversely affected by oxidized conditions, but it was species- and strain-dependent. The E h caused the change of metabolic routes of the microorganisms and, thereby, the change of volatile compounds and organic acids contents of kefir. Principal component analysis (PCA) of the volatile compounds separated the kefirs according to the culture and redox status. Kefirs with low E h were characterized by the presence of sulphur compounds, whereas kefirs with oxidative E h were characterized mainly by aldehydes and diacetyl. In addition, reduced E h caused arising in sensory preference of the kefir samples. Highlights: The complex flora of kefir responded differently under different redox conditions. E h influenced viability of kefir microorganisms as species- and strain-dependent. Organic acids and volatile compounds profile varied due to E h and kefir culture. Low E h were required to obtain balanced flavour and desirable sensory properties. Standardizing of E h during fermentation may allow to improvement of kefir quality.